2019
DOI: 10.1186/s13030-019-0162-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a childhood eating disorder outcome scale

Abstract: We developed and validated a childhood eating disorder outcome scale based on outcomes associated with body mass index standard deviation score (BMI-SDS). This prospective observational study included 131 children with eating disorders (aged 5–15 years). Participants’ outcomes scales were completed at the first visit and at 1, 3, 6, and 12 months. The scale evaluated 12 outcomes: body weight change (BW), eating attitude (EA), fear of being fat (FF), body image distortion (BD), menstruation (ME), perceived phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
2
0
2
Order By: Relevance
“…In a previous study, our members demonstrated a signi cant negative correlation between the outcome scale and the BMI-SDS, and changes in outcome scale scores from baseline to 12 months were signi cantly associated with BMI-SDS improvement [22]. To the best of our knowledge, this scale is the rst statistically analyzed outcome measure in children with eating disorders.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In a previous study, our members demonstrated a signi cant negative correlation between the outcome scale and the BMI-SDS, and changes in outcome scale scores from baseline to 12 months were signi cantly associated with BMI-SDS improvement [22]. To the best of our knowledge, this scale is the rst statistically analyzed outcome measure in children with eating disorders.…”
Section: Discussionmentioning
confidence: 63%
“…Members of the J-PED study discussed the outcome scale items and, as a result of factor analysis, the core symptoms of eating disorders (eating attitudes (EA), fear of being fat (FF), body image distortion (BD)), and the biopsychosocial factors, which covered items in physical and psychological areas based on environmental factors speci c to children (body weight change, menstruation (ME), perception of physical condition, school attendance (SA), disease recognition of school (RS), family functioning (FA), disease recognition by parent (RP), social adaption (SA), and relationships with friends (RF)). After that, an outcome scale was developed by excluding ME, RS, and RP, which had small loadings as a result of factor analysis [22]. The childhood eating disorder outcome scale has total scores ranging from 0 to 36, with 36 being the worst.…”
Section: Childhood Eating Disorder Outcome Scalementioning
confidence: 99%
“…Na população infantil, dados epidemiológicos como a porcentagem da amostra por transtornos alimentares são relativamente pouco divulgados ou até mesmo pesquisados. Nagamitsu et al (2019) relataram que casos na infância em transição para a adolescência tangem 1%. Levando em conta estes achados, alguns dos principais fatores envolvidos no surgimento e prevalência de quadros de transtornos alimentares em crianças são o medo de engordar (Ataş-Berksoy et al, 2018), distorção de imagem (Ataş-Berksoy et al, 2018;Chatoor et al, 2019), questões familiares, como a morte de algum dos cuidadores (Larsen et al, 2018), influência de hábitos alimentares dos pais refletido no desenvolvimento do transtorno infantil (Lydecker & Grilo, 2016), transtornos psíquicos e fatores genéticos (Larsen et al, 2018), sendo os transtornos comumente iniciados no desenvolvimento da autonomia da criança em se alimentar sozinha (Lucarelli et al, 2017).…”
unclassified
“…Quando correlações significativas entre o gênero de crianças e transtornos alimentares gerais na infância são analisadas, não é identificada uma prevalência (Aldridge et al, 2015;Copeland et al, 2015;Crapnell et al, 2015;Dmitrzak-Węglarz et al, 2019), sendo as relações mais visíveis em trans-tornos específicos. Os transtornos recorrentes em crianças são compulsão alimentar periódica, anorexia e bulimia associadas; meninos compõem a maioria nas amostras de compulsão, e meninas destacam-se nos demais itens (Moura et al, 2015;Lucarelli et al, 2017;Laporta-Herrero & Latorre, 2019;Nagamitsu et al, 2019).…”
unclassified